2017
DOI: 10.19080/ofoaj.2017.03.555623
|View full text |Cite
|
Sign up to set email alerts
|

Water Analysis of River Siang of Arunachal Pradesh, India

Biplab Kumar Das

Abstract: Assessments of physico-chemical parameters were carried out during 2012 to 2014. A major and important different water quality parameters were measured in all collected samples, including Water Colour, Air Temperature, Water Temperature, Na + , Ca 2++ , Mg 2+ and Zn 3+ , Fe 3+ and some major anions like Cl -, SO 4 2-, CO 3 2and SO 4 2-. The results that are recorded in the different stations are compared with the different seasons and also with the different year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Another similar study in South India assessed the metal contents of ground water revealing safe metal limits 8 . Similar studies in other water bodies of Arunachal Pradesh such as Kameng river 9 , Siang river 10 , and groundwater of Itanagar 11 have also been carried out. All these studies have raised caution about the increasing contamination level of these water bodies.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Another similar study in South India assessed the metal contents of ground water revealing safe metal limits 8 . Similar studies in other water bodies of Arunachal Pradesh such as Kameng river 9 , Siang river 10 , and groundwater of Itanagar 11 have also been carried out. All these studies have raised caution about the increasing contamination level of these water bodies.…”
Section: Introductionmentioning
confidence: 66%
“…These high contents were attributed to weathering, dissolution and mineralization of rocks 9 . A study on the Siang River reported the presence of various metals in high amounts resulting from excessive use of fertilizers and pesticides 10 . Another study in Itanagar which analysed groundwater samples reported Cr contamination that was three times higher than the WHO recommended values 11 .…”
Section: Discussionmentioning
confidence: 99%